2018
DOI: 10.1016/j.btre.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Smoke produced from plants waste material elicits growth of wheat ( Triticum aestivum L.) by improving morphological, physiological and biochemical activity

Abstract: HighlightsSmoke produced from plants waste material is more efficient, cost effective, vegetative growth promoter, inexpensive, rapid and most appropriate eco-friendly bio-fertilizer in sustainable agriculture.Plant derived smoke was generated by burning of plant material (leaf, straws etc) in a specially designed furnace.Four level of plant derived smoke (1 h, 2 h, 3 h & 4 h) along with control were tested on four wheat cultivars in CRD repeated pot experiment.Plant derived smoke exposure applied for short ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The use of organic fertilizers and herbicides in agriculture is recently among the important applications. Therefore, the demand for natural resources for sustainable agriculture has been increasing steadily (Iqbal et al, 2017). In this study, it was observed that the smoke solutions derived from wheat straw significantly affected the germination, seedling growth, and chemical composition of grass pea.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The use of organic fertilizers and herbicides in agriculture is recently among the important applications. Therefore, the demand for natural resources for sustainable agriculture has been increasing steadily (Iqbal et al, 2017). In this study, it was observed that the smoke solutions derived from wheat straw significantly affected the germination, seedling growth, and chemical composition of grass pea.…”
Section: Discussionmentioning
confidence: 84%
“…Smoke contains some compounds that inhibit germination and thus has different effects on different species (Drewes et al, 1995). Similarly, morphological, physiological, and biochemical characteristics were influenced when smoke was applied to wheat seeds; some characteristics, such as root length, shoot length, leaf area, and chlorophyll content, were reported to increase significantly and the wheat genotypes had different responses to smoke solutions (Iqbal et al, 2017). The same authors also determined that short-term smoke application (1-2 h) yielded better results than longterm applications(3-4 h).…”
Section: Discussionmentioning
confidence: 99%
“…Cvjetko et al [54] observed a decrease in MDA level and electrolyte leakage due to exogenous application of AgNPs in tobacco plants. Iqbal et al [55] reported an increase in RWC and membrane stability in wheat plants treated with plant‐derived smoke. A profound increase takes place in photosynthetic pigments such as chlorophyll and carotene contents of microalgae ( Chlorella vulgaris ) due to AgNPs treatment [56].…”
Section: Resultsmentioning
confidence: 99%
“…Also, Adkins & Peters (2001) found that the optimal concentration of SS were different for promoting the germination of Avena fatua and Malvane glecta. It is reported that aerosol smoke treatment at different periods (1, 2, 3 and 4 h) significantly improved root length (2.6%), shoot length (7.7%) and leaf area (63.9%) in four wheat cultivars, and this effect was observed in short time exposures (1-2 h) and varied amongst cultivars (Iqbal et al, 2017). In addition, positive effects were determined at low concentrations and toxic effects of high concentrations were reported almost in all the studies on smoke solutions.…”
Section: Discussionmentioning
confidence: 96%